De novo expression of CD44 in prostate carcinoma is correlated with systemic dissemination of prostate cancer. Issue 11 (November 1998) - Paradis, V; Eschwège, P; Loric, S; Dumas, F; Ba, N; Benoît, G; Jardin, A; Bedossa, P
Abstract : AIMS: To evaluate the role of CD44 in early steps in the development of prostate cancer, and to assess the biological significance of preneoplastic lesions in prostate cancer. METHODS: 38 patients with clinically localised prostate cancer were studied. The standard form of CD44 (CD44H) and v6 isoform expressions were semiquantitatively evaluated on paraffin embedded tumour tissue by immunohistochemistry. Disseminated prostatic cells were detected by prostate specific membrane antigen reverse transcriptase polymerase chain reaction in the blood of each patient before radical prostatectomy. RESULTS: In normal or benign prostate glands, only basal cells showed CD44H and v6 labelling. Fourteen of the 38 prostate cancers (37%) had CD44H membranous staining of prostatic tumour cells. In 18 patients (47%), circulating prostatic cells were detected in blood before surgery. Although no correlation between the expression of CD44 and the Gleason score or staging was observed, a significant correlation was found between the expression of CD44H by tumour cells and prostatic cell blood dissemination (p = 0.04). In 28 cases, foci of prostatic intraepithelial neoplasia were observed, and nine had CD44H immunostaining. CONCLUSIONS: De novo expression of CD44 by prostatic tumour cells is associated with systemic dissemination of prostate cells independently of pathological criteria.